Evolved Eugenics and Reinforcement of “Othering”: Renewed Ethico-Legal Perspectives of Genome Editing in Reproduction - Pin Lean Lau (BioTech, 2023)
This article extends an exploration into renewed ethico-legal perspectives of genome editing technologies, examined from an evolved conceptualization of eugenics in contemporary human reproduction. Whilst the ethico-legal conundrums presented by genome-editing technologies in various aspects of modern medicine have thus far inspired a comprehensive trove of academic scholarship—and notwithstanding the World Health Organization’s (WHO) publication of guidelines on human genome editing in 2021—the legislative landscape for these technologies remain relatively unchanged. Accordingly, this paper presents the unresolved problematic questions that still require significant reflection. First, the paper highlights these questions, which primarily center around the tension between reproductive autonomy and the legal governance of reproductive/genome editing technologies by a democratic state. Secondly, the paper interrogates the evolved conceptualization of eugenics, exercised on the part of prospective parents as part of reproductive autonomy. By this, the paper predicates that it indirectly reinforces societal and systemic problems of discrimination and “othering”, increasing reproductive inequalities in excluded communities. Thirdly, the paper attempts to offer narratives of intersectionality as a facilitating tool in a continuing dialogue to build belonging, foster a healthy and balanced exercise of reproductive autonomy, and increase reproductive equalities.